The Meaning of Social Justice - Puno, Reynato (Social Sciences and Development Review, 2012)
This paper showcases the context of social justice as well as the development of modern concept of inclusive distributive justice. Looking at treaties, protocols, and universal human rights as bases of fundamental objective of the right to life and the dignity of human persons, as well as in lay man’s term, it touches the concepts of primary social goods such as rights, liberty, and opportunity. Essentially, summarizing the term as opportunities and aspects of institutions that the citizens should have in order to live a sense of their own worth as moral persons and thereby, realizing the individual’s highest interest and advancing people’s self-confidence and self-worth.
Keywords: social justice; rights and liberty; inclusive distributive justice